Performance Measures for a three-unit compact circuit (International Journal of Engineering and Computer Science, 2015)
This paper analyses a three component system with single repair facility. Denoting the failure times of the components as T1 and T2 and the repair time as R, the joint survival function of (T1, T2, R) is assumed to be that of trivariate distribution of Marshall and Olkin. Here, R is an exponential variable with parameter α and T1 and T2 are independent of each other. In this paper use of Laplace-Transform is taken for finding Mean Time Between Failure, Availability and Mean Down Time and table for Reliability measure is shown in the end.